Glandular and Cystic Bladder Cystitis: Case Report and Review of the Literature - M., Darouichi (Journal of Digestive Disorders And Diagnosis, 2020)
Glandular-cystic bladder cystitis is a rare, benign non-tumor condition, preferentially located on the area of the bladder trigone and can simulate a malignant tumor. It is a benign reactive metaplasia of the bladder submucosa, characterized by hyperplasia of the islets of Von Brunn and cystic. It is classified among reactive epithelial anomalies of the urothelium, such as islet hyperplasia of Von Brünn, cystitis, glandular cystitis, nephrogenic metaplasia and epidermoid metaplasia. It presents a clinical diagnostic challenge having the expression of a simple recurrent cystitis and misleading the radiological diagnosis evoking a malignant tumor of the bladder. Its certainty diagnosis is histological. We report the case of a 38-year-old young man who consulted for recurrent cystitis. The CT scan showed a vegetative tissue structure of the middle and left medial vesical floor, sawtooth 3 cm long axis suspecting a tumor of the bladder. The patient underwent transurethral resection of the bladder lesion. The histological and immunohistochemical examination concluded with glandular and cystic cystitis (minor form). In the light of this observation, we will discuss the diagnostic difficulties, the pathophysiological mechanisms, the radiological aspects, the anatomopathological, therapeutic features and the prognosis of this rare condition. The literature regarding this entity has been reviewed and the differential diagnosis was discussed.
Keywords: glandular cystitis; cystic cystitis; radiology; differential diagnosis; anatomopathological; treatment.